Main Tendencies in Preparing PhD Dissertations in Social Sciences and Humanities in Turkey - Yusuf Alpaydın; Mahmut Hakkı Akın (İnsan & Toplum)
Turkish doctorate programs are mainly composed of course work, preliminary examination, and dissertation stages. In these stages, naturally, several traditions and approaches are followed in different universities and graduate institutes. In this study, it is aimed to identify the main tendencies in preparing PhD dissertations in humanities and social sciences and to analyze the current situation in terms of production of academic knowledge and academic institutionalization in Turkey. Towards, the preparation processes for preliminary examinations and their contents, the procedures for the selection of advisors, dissertation subjects and research methodologies, and rationale for the study subjects, preference of research methodologies and academic writing techniques, and lastly relations with advisors and dissertation committee members are chosen for investigation. Quantitative methodology and survey technique has been used in the study to reach people who have completed their doctoral study on humanities and social sciences in 2011, 2012 and 2013 years in ten Turkish Universities that have given most doctoral graduates in social sciences. 405 people have responded the questionnaire form. The results indicate that the main motive behind selecting dissertation topics is related to career advancement, i.e securing a good position within the university system. Study found that systematic literature review is the most used research methodology and the reading-noting of all related sources than starting to write according to the materials is the most used academic writing technique in dis- sertations. Also, it is found that 1/3 of the participants had no chance to choose his/her advisors. Most of them perceived their relationship with their advisors positively, while admitting that the rate of advisors who actively contributed to the writing process is only 45 %.